2004
DOI: 10.1002/app.21299
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cesium‐134 and cobalt‐60 with radiation‐grafted copolymers from their liquid wastes

Abstract: ABSTRACT:The introduction of new characteristics to some synthetic polymers was achieved through the ␥-radiation-induced graft copolymerization of an acrylamide/vinyl acetate comonomer onto polypropylene films for the preparation of synthetic membranes. The influence of the reaction conditions on the grafting yield, such as the solvent and its composition and the inhibitor and its concentration, was investigated. An alkaline treatment was carried out for the prepared graft copolymer to improve its ion-exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…For unirradiated, irradiated and LDPE graft copolymer prepared in methanol, there are mainly two crystalline peaks in the XRD patterns; one in the angular range (2θ) of 21-22⋅4° and another in the range 35⋅4-35⋅8°. These results suggested that the inherent crystallinity of the backbone polymer was not employed by the graft copolymerization of MMA and that the grafting occurred only in the amorphous regions (Toi et al 1976;Hegazy et al 2005). These peaks are well characterized in LDPE and correspond to specific crystallographic planes 110 and 200 (Chattopadhy et al 2001).…”
Section: Structural Characterizationmentioning
confidence: 92%
“…For unirradiated, irradiated and LDPE graft copolymer prepared in methanol, there are mainly two crystalline peaks in the XRD patterns; one in the angular range (2θ) of 21-22⋅4° and another in the range 35⋅4-35⋅8°. These results suggested that the inherent crystallinity of the backbone polymer was not employed by the graft copolymerization of MMA and that the grafting occurred only in the amorphous regions (Toi et al 1976;Hegazy et al 2005). These peaks are well characterized in LDPE and correspond to specific crystallographic planes 110 and 200 (Chattopadhy et al 2001).…”
Section: Structural Characterizationmentioning
confidence: 92%
“…As a result, non-precipitation methods like ion-exchange have been investigated as possible methods to remove radioactive cesium from wastewater [1][2][3]. Natural and synthetic zeolites have been analyzed for their ion-exchange properties with cesium for decades.…”
Section: Introductionmentioning
confidence: 99%